Authigenic carbonates from cold seep sites in the Laptev Sea: 230Th/U chronology and insights into fluid sources; Marine Geoscience and Energy Resources; Vol. 188 - Ruban A. S. Aleksey Sergeevich; Maksimov F. E. Fedor Evgenjevich; Rudmin M. A. Maksim Andreevich; Yakich T. Yu. Tamara Yurievna; Nikolaeva A. N. Anastasiya Nikolaevna; Dudarev O. V. Oleg Viktorovich; Semiletov I. P. Igor Petrovich (2026, 2026)
This study focuses on authigenic carbonates formed under methane seepage on the outer shelf and continental slope of the Laptev Sea. Mineralogically, the carbonates are mainly represented by high-Mg calcite, as well as dolomite and kutnohorite. The δ13C values range from −53.0‰ to −27.1‰ V-PDB, suggesting the possible involvement of methane of different origins in carbonate formation. The wide range of δ13C values, combined with morphological variations, may reflect temporal changes in the composition of methane-containing fluids, likely associated with variable contributions from biogenic and thermogenic sources. The highest δ18O values (up to 6.8‰ V-PDB) were recorded in samples from the continental slope, which also display the lightest carbon isotope compositions. Such a relationship may suggest that an increased contribution of biogenic methane to the fluid is accompanied by higher δ18O values in the resulting carbonates. This likely reflects the participation of methane released during the dissociation of gas hydrates that existed on the continental slope. Elevated 87Sr/86Sr ratios (up to 0.709583) in some samples indicate an additional source of radiogenic strontium, which may be related to the migration of deep methane-containing fluids. 230Th/U dating results indicate that carbonate formation occurred within the past 5 ka. On the outer shelf, ages range from 5.0 ± 0.3 to 2.6 ± 0.4 ka, while on the continental slope they range from 2.7 ± 0.3 to 2.1 ± 0.2 ka. These age intervals indicate a pulsating nature of methane discharge and differences in its onset timing. The discharge of methane-containing fluids in different parts of the Laptev Sea may have been triggered by several partially overlapping factors, including tectonic fault activity, submarine permafrost degradation, and seismic events